Micropropagation and Conservation of Fig (Ficus Carica L.) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
An efficient protocol is outlined for rapid and mass micropropagation of Ficus carica L. (fig). Shoot tips (5 mm) were obtained from mother plants stock grown on half strength Murashige and Skoog (½ MS) medium with the addition of 30 g/L sucrose. For shoot multiplication Benzyl amino purine (BAP) and kinetin produced differences number of new shoot per plant and shoot height. BAP at 0.4 mg/L in combination with 0.2 mg/L indole-3-butyric-acid (IBA) produce maximum in vitro propagation rate, with 4.2 shoots per ex-plant. Root initiation was experimented on MS medium containing different concentrations of mg/L, IBA, IAA (Indole-3-acetic-acid) (IAA) or Naphthalene acetic acid (NAA). Highest number of root (4.3) was resulted when 1.5 mg/L IBA was used. After acclimatization in a mixture of (1 soil: 1 perlite: 1 peat) survival rate of 80% was achieved. For in vitro conservation of F. carica was experimented as microshoots were stored for 40 weeks on MS medium containing different sucrose concentration. Medium supplemented with 3% sucrose gave the highest regrowth (89%) at 24 ± 2 °C. Culture grew slowly when transferred to new fresh medium after the storage periods.